Concentration and Community of Airborne Bacteria in Response to Cyclical Haze Events During the Fall and Midwinter in Beijing, China - Li, Weilin; Yang, Jinshui; Zhang, Daizhou; Li, Baozhen; Wang, Entao; Yuan, Hongli (Frontiers in Microbiology, 2018)
Since 2013, severe haze events frequently have occurred in Beijing between October and March, which have created a significant public health threat. Although variations in the chemical composition of these haze events have been studied widely, information pertaining to airborne bacteria in such haze events remains limited. In this study, we characterized the concentration, community structure, and composition of the airborne bacteria in response to nine haze events that occurred between October 1, 2015, and January 5, 2016. We also analyzed the correlations of airborne bacteria (concentration, community structure, and composition) with pollution levels and meteorological factors. The results indicated that airborne bacterial concentration showed a positive cyclical correlation with the haze events, but the bacterial concentration plateaued at the yellow pollution level. In addition, we found particulate matter (PM10) and relative humidity to be key factors that significantly affected the airborne bacterial concentration and community structure. Moreover, Halomonas and Shewanella were enriched on haze days for all nine of the haze events. Finally, the correlations between haze pollution and airborne bacteria in midwinter were weaker than those in fall and early winter, indicating an obvious staged distinction among the effects of haze on airborne bacteria. Our study illuminated the dynamic variation of bioaerosols corresponding to the cyclical haze events and revealed the interactions among air pollution, climate factors (mainly relative humidity), and airborne bacteria. These results imply that different strategies should be applied to deal with the potential threat of airborne bacteria during haze events in different seasons.